PERANCANGAN MESIN PEMIPIL JAGUNG RAMAH LINGKUNGAN DENGAN PENDEKATAN NORDIC BODY MAP - Firman Ardiansyah Ekoanindiyo; Antoni Yohanes; Endro Prihastono (Universitas Putera Batam, 2020)
Based on calculations by the Directorate General of Food Plants (Ditjen TP), Ministry of Agriculture. Corn production in the last 5 years has increased by an average of 12.49% per year. According to the Secretary of the Directorate General of Food Crops of the Ministry of Agriculture (Kementan) Maman Suherman in 2019 maize production is estimated to reach 33 million tonnes of dry shell (PK) in an interview with Republika on January 6, 2019. Cepiring sub-district, Kendal district, apart from being planted with rice in the rainy season, rice fields also planted with maize. After harvesting, the corn that has been plucked is separated from the cob using a corn sheller. The shelling machine is used using diesel fuel and electricity, with workers standing for long periods of time, causing fatigue in the arms, waist, thighs and back. The data processing of the nordic body map questionnaire was carried out to determine the complaints on the skeleton and muscles of the workers. From the results of the questionnaire above, most Sido Rejo farmers feel complaints on their right shoulder, left upper arm, back, right upper arm, back, waist, left elbow, right elbow, left forearm, right forearm, left wrist, wrist right, left hand, right hand, left thigh, right thigh, left calf, right calf, left leg to right leg. With anthropometric measurements, the dimensions of the body used are the height of the sitting shoulders and the data used are the average data or the 50th percentile. With this solar sheller, it can save fuel and be environmentally friendly and reduce the complaints of the frame and muscles of farmers